Family engagement in the care of infectious patients in intensive care units: A hybrid concept analysis - Mohsen Soleimani; Ali Fakhr‐Movahedi; Sajad Yarahmadi (Wiley, 2024)
Abstract Aim This study aims to define and investigate characteristics, antecedents, and consequences of the concept of family engagement in caring for patients with infectious diseases hospitalised in intensive care units. Design This is a three‐phase hybrid model study (theoretical, fieldwork, and analytical phase). Methods The York University Guidelines were used in the theoretical phase, and ultimately, 16 pieces of literature related to the subject under study from 2011 to 2021 were reviewed. The content analysis was used for fieldwork phases; eight participants were interviewed. Then, the theoretical and fieldwork findings were compared, integrated, and analysed. Results This concept has characteristics such as; awareness, belief, perception, and willingness of the nurse to engage the family; a sense of responsibility, willingness, and sacrifice of the family; the physical or virtual presence of the family; triangular interaction between the nurse, patient, and family; perception and identifying the goals; education and information transfer; team collaboration; delegation of responsibility to the family; decision making; and protection of the family. Antecedents include the availability of infrastructure; patient, family, and nurse conditions; and the quality implementation of engagement. The consequences include positive consequences related to the patient, family, nursing, and society, as well as some negative consequences. This study provided a comprehensive perception of family engagement in the care of patients with infectious diseases in intensive care units and defined it more clearly, showing its characteristics, antecedents, and consequences. Patient or Public Contribution Eight participants were interviewed, including five nurses, two family caregivers, and one patient.